Comparison of newer generation self-expandable vs. balloon-expandable valves in transcatheter aortic valve implantation: the randomized SOLVE-TAVI trial - Thiele, Holger; Kurz, Thomas; Feistritzer, Hans-Josef; Stachel, Georg; Hartung, Philipp; Eitel, Ingo; Marquetand, Christoph; Nef, Holger; Doerr, Oliver; Lauten, Alexander; Landmesser, Ulf; Abdel-Wahab, Mohamed; et al. (European heart journal, 2020)
Transcatheter aortic valve implantation (TAVI) has emerged as established treatment option in patients with symptomatic aortic stenosis. Technical developments in valve design have addressed previous limitations such as suboptimal deployment, conduction disturbances, and paravalvular leakage. However, there are only limited data available for the comparison of newer generation self-expandable valve (SEV) and balloon-expandable valve (BEV). SOLVE-TAVI is a multicentre, open-label, 2 × 2 factorial, randomized trial of 447 patients with aortic stenosis undergoing transfemoral TAVI comparing SEV (Evolut R, Medtronic Inc., Minneapolis, MN, USA) with BEV (Sapien 3, Edwards Lifesciences, Irvine, CA, USA). The primary efficacy composite endpoint of all-cause mortality, stroke, moderate/severe prosthetic valve regurgitation, and permanent pacemaker implantation at 30 days was powered for equivalence (equivalence margin 10% with significance level 0.05). The primary composite endpoint occurred in 28.4% of SEV patients and 26.1% of BEV patients meeting the prespecified criteria of equivalence [rate difference -2.39 (90% confidence interval, CI -9.45 to 4.66); Pequivalence = 0.04]. Event rates for the individual components were as follows: all-cause mortality 3.2% vs. 2.3% [rate difference -0.93 (90% CI -4.78 to 2.92); Pequivalence < 0.001], stroke 0.5% vs. 4.7% [rate difference 4.20 (90% CI 0.12 to 8.27); Pequivalence = 0.003], moderate/severe paravalvular leak 3.4% vs. 1.5% [rate difference -1.89 (90% CI -5.86 to 2.08); Pequivalence = 0.0001], and permanent pacemaker implantation 23.0% vs. 19.2% [rate difference -3.85 (90% CI -10.41 to 2.72) in SEV vs. BEV patients; Pequivalence = 0.06]. In patients with aortic stenosis undergoing transfemoral TAVI, newer generation SEV and BEV are equivalent for the primary valve-related efficacy endpoint. These findings support the safe application of these newer generation percutaneous valves in the majority of patients with some specific preferences based on individual valve anatomy.